Quartz crystal microbalance-based biosensing of hepatitis B antigen using a molecularly imprinted polydopamine film - Lim, Hui Jean; Saha, Tridib; Tey, Beng Ti; Tan, Wen Siang; Syed Hassan, Sharifah; Ooi, Chien Wei (Elsevier, 2022)
Quartz crystal microbalance (QCM)-based biosensors are highly attractive as rapid diagnostic devices for detecting infectious diseases. However, the fabrication of QCM-based biosensors often involves tedious processes due to the poor stability of the biological recognition elements. In this work, the simple self-polymerisation of dopamine was used to functionalise the QCM crystal surface with a molecularly imprinted polydopamine (MIPDA) sensing film for detecting the hepatitis B core antigen (HBcAg), a serological biomarker of hepatitis B. Recognition cavities that complemented the size and shape of HBcAg were observed on the QCM crystal surface after functionalisation with the MIPDA film. The MIPDA-QCM biosensor showed a selective affinity for HBcAg, recording frequency responses up to 7.8 folds larger towards HBcAg compared to human serum albumin at the same analyte concentrations. The biosensor response was enhanced by using the optimal concentrations of 10 mg mL−1 of dopamine and 1 mg mL−1 of template for MIPDA film formation, resulting in a low detection limit (0.88 μg mL−1) that enables the detection of clinically relevant titres of HBcAg. The detection process could be completed within 10 min after sample loading without additional steps for signal amplification, highlighting the practical advantages of the MIPDA-QCM biosensor for point-of-care detection of hepatitis B.